Identification of Performance Achievements of LPP-RRI Batam Employees as Management Strategy Effectiveness Institutional Conflict - Adnan, A.; Luran, Muhammad Fadli; Amirullah, A. (Manunggal Halim Jaya, 2025)
This research began with the author's suspicions about the number of human resource problems at LPP-RRI Batam as a research locus. The problem identified based on the initial survey is the positive significance of the work culture variable through work motivation and employee workload on conflict management at LPP-RRI Batam. The basis for identifying initial problems was used for further research to provide alternative solutions to institutional problems at LPP-RRI Batam. The research target focuses on partial and simultaneous analysis of the influence of work culture variables through work motivation and employee workload on conflict management at LPP-RRI Batam as the locus studied. A quantitative approach is a supporting tool for achieving the research findings target, which is expected to have empirical and practical benefits when the research findings are concluded. Data was collected by observing and distributing a structured list of questions in the questionnaire. The data was analyzed using descriptive techniques supported by path or path analysis. Implement data analysis Structural Equation Modelling and PLS to support data analysis descriptions. Research findings indicate the positive significance of work culture variables through work motivation and team member workload on conflict management at LPP-RRI Batam.